2006
DOI: 10.1207/s15327876mp1803s_2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Brief Situational Awareness Training in a Police Shooting Simulator: An Experimental Study

Abstract: The aim of this study was to investigate the effect of situational awareness (SA) training in a shooting simulator. Forty 1st-year students from the Norwegian Police University College participated in this study. They were divided into 2 groups and matched with respect to sex and previous weapon experience. The SA-trained group received scenario-based training with freeze technique and reflection based on the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 27 publications
2
75
0
Order By: Relevance
“…Our assessment of the quality of training is based on information gathered in the following three ways: review of the literature on police training (see, for comparison, Bennell and Jones, 2005;Helsen and Starkes, 1999;Morrison and Vila, 1998;Saus et al, 2006) review of the training materials provided by the NYPD, including lesson plans, tests, and evaluation forms from the hands-on workshops and lessons observations of a number of workshops and lessons in the skills and abilities term, including stop, question, and frisk; car stop; ground tactics; firearm retention; straight-baton lessons; basic tactical firearm training; situational simulations (i.e., scenario-based training) using the Meggitt FATS simulator; the tactical house; the tactical village with Simunition systems; and the mock-precinct exercises). Also, for comparison, we observed firearm and tactical training at two large police departments and one large sheriff's department in other cities.…”
Section: Methods Of Assessmentmentioning
confidence: 99%
“…Our assessment of the quality of training is based on information gathered in the following three ways: review of the literature on police training (see, for comparison, Bennell and Jones, 2005;Helsen and Starkes, 1999;Morrison and Vila, 1998;Saus et al, 2006) review of the training materials provided by the NYPD, including lesson plans, tests, and evaluation forms from the hands-on workshops and lessons observations of a number of workshops and lessons in the skills and abilities term, including stop, question, and frisk; car stop; ground tactics; firearm retention; straight-baton lessons; basic tactical firearm training; situational simulations (i.e., scenario-based training) using the Meggitt FATS simulator; the tactical house; the tactical village with Simunition systems; and the mock-precinct exercises). Also, for comparison, we observed firearm and tactical training at two large police departments and one large sheriff's department in other cities.…”
Section: Methods Of Assessmentmentioning
confidence: 99%
“…However, Saus et al (2006) have found empirical evidence substantiating the effects of the SA training Table 1 Comparison of emphasis shift training, situation awareness training, and drill and practice.…”
Section: Sa Trainingmentioning
confidence: 99%
“…Emphasis shift training (Gopher, 2007;Gopher et al, 1989) Situation awareness training (Endsley and Robertson 2000;Saus et al, 2006) Drill and practice (Carlson et al, 1989;Ericsson et al, 1993) Rationale Learning through priority changes on subcomponents of a whole task Learning through randomized ''freezing" of a task with situation awareness questions and debriefing they designed for students of a police university on the basis of a ''freezing" technique coupled with debriefing. This approach calls for randomly stopping, or freezing, a simulated task, posing the participant questions about the three levels of SA (Endsley, 1995b), then debriefing the individual.…”
Section: Descriptionmentioning
confidence: 99%
See 2 more Smart Citations